The Effect of Climate Change and Adaptation Policy on Agricultural Production in Eastern Africa - Goytom Abraha Kahsay; Lars Gårn Hansen (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2014)
We estimate the production function for agricultural output in Eastern Africa incorporating climate variables disaggregated into growing and non-growing seasons. We find a substantial negative effect of within growing season variance of precipitation. We simulate predicted climate change for the region and find a resulting output reduction of between 1.2% and 4.5%. We also find substantial potential for mitigating the effects of within growing season precipitation variability through conventional technologies such as flexible planting and rainwater harvesting that substantially exceeds the potential loss from predicted climate change.
Keywords: Q18; Q54; O55; E23; O13; R11; 330; Climate change; adaptation policy; Eastern Africa; agricultural production